Silent Allies: Endophytic Entomopathogenic Fungi Promote Biological Control and Reduce Spittlebug Mahanarva spectabilis Distant, 1909 (Hemiptera: Cercopidae) - Michelle O. Campagnani; Luís Augusto Calsavara; Charles Martins de Oliveira; Alexander Machado Auad (Journal of Fungi, 2025)
Urochloa ruziziensis (R. Germ. and C.M. Evrard) Crins (synonym Brachiaria ruziziensis) Poales: Poaceae) pastures are often attacked by spittlebugs, compromising their biomass for livestock usage. A sustainable control method involves the use of entomopathogenic fungi. Therefore, the objective of this study was to evaluate the efficacy of controlling Mahanarva spectabilis Distant, 1909 (Hemiptera: Cercopidae), in greenhouse and field conditions via endophytic entomopathogenic fungi. In the greenhouse, the mortality of nymphs and adults was 100%, and more than 53% of the nymphs and 59% of the adults that fed on plants inoculated with Fusarium multiceps and Metarhizium anisopliae presented with these fungi in their cadavers. In the field, more than 45% of the insect cadavers that had fed on plants grown from fungus-treated seeds were found to contain the fungi. F. multiceps was found to be endophytic in more than 60% of the plants up to 90 days after seed treatment, and M. anisopliae was found in more than 70% of the plants up to 120 days after treatment. The damage scores of the control plants, both in the greenhouse and in the field, were greater than those of the plants inoculated with the fungi. F. multiceps and M. anisopliae in the endophytic pathway of U. ruziziensis are therefore efficient at controlling spittlebugs.